Iatrogenic Lower Extremity Subcutaneous Emphysema after Prolonged Robotic-Assisted Hysterectomy - Monica Hagan Vetter; Chelsea Mutscheller; Joel Cardenas-Goicoechea (Case Reports in Obstetrics and Gynecology)
Subcutaneous emphysema is a known complication of carbon dioxide insufflation, an essential component of laparoscopy. The literature contains reports of hypercarbia, pneumothorax, or pneumomediastinum. However, isolated lower extremity subcutaneous emphysema remains a seldom-reported complication. We report a case of unilateral lower extremity subcutaneous emphysema following robotic-assisted hysterectomy, bilateral salpingooophorectomy, staging, and anterior/posterior colporrhaphy for carcinosarcoma and vaginal prolapse. On postoperative day 1, the patient developed tender crepitus and bruising of her right ankle. Radiography confirmed presence of subcutaneous air. Vital signs and laboratory findings were unremarkable. Her symptoms spontaneously improved over time, and she was discharged in good condition on day 2. In stable patients with postoperative extremity swelling or pain with crepitus on exam, the diagnosis of iatrogenic subcutaneous emphysema must be considered.